2018
DOI: 10.1016/j.icarus.2018.04.031
|View full text |Cite
|
Sign up to set email alerts
|

The sublimative torques of Jupiter Family Comets and mass wasting events on their nuclei

Abstract: Sublimative outgassing of comets produces torques that alter the rotation state of their nuclei. Recently, parameterized sublimative torque models have been developed to study rotation state changes of individual comet nuclei and populations of cometary bodies. However, these models simplify the interactions between the escaping gas and cometary surface into only a few parameters that hide the details of these complex interactions. Here we directly compare the Xparameter model (Samarasinha & Mueller, 2013) wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 94 publications
3
26
0
Order By: Relevance
“…Prialnik et al 2004), sublimative torques that can spin up nuclei and trigger mass wasting or splitting (e.g. Steckloff & Jacobson 2016;Steckloff & Samarasinha 2018), and localized erosion that can induce mass loss (e.g. Vincent et al 2017).…”
Section: Evolving Back and Forth Between The Centaurs And Jfcsmentioning
confidence: 99%
“…Prialnik et al 2004), sublimative torques that can spin up nuclei and trigger mass wasting or splitting (e.g. Steckloff & Jacobson 2016;Steckloff & Samarasinha 2018), and localized erosion that can induce mass loss (e.g. Vincent et al 2017).…”
Section: Evolving Back and Forth Between The Centaurs And Jfcsmentioning
confidence: 99%
“…Cliff collapse is an important process that reshapes the nucleus surface of a comet (Britt et al 2004;Pajola et al 2015Pajola et al , 2016Pajola et al , 2017Steckloff et al 2016;Steckloff & Samarasinha 2018;Lucchetti et al 2019). The morphology of the associated deposits is controlled by different factors such as the topography, the slope, the mechanical properties of the collapsing material, the presence of volatiles, and the insolation conditions (Cruden 1996;Martha et al 2010;Hungr et al 2013).…”
Section: Possible Chronologymentioning
confidence: 99%
“…From December 2014 to June 2016, tens of morphological changes have been observed. Changes arise as a modification or a creation of new landscapes on the surface; in particular, cliff collapse appears to be a key process that reshapes the surface (Britt et al 2004;Pajola et al 2015Pajola et al , 2016Pajola et al , 2017Steckloff et al 2016;Steckloff & Samarasinha 2018;Lucchetti et al 2019). In the Imhotep region Groussin et al (2015b) observed morphological changes in the form of roundish features growing in a preferential direction.…”
Section: Introductionmentioning
confidence: 99%
“…On 67P, multiple landslide deposits are identified in close association with cliffs. These observations suggest that cliff collapse is an important process in reshaping cometary surfaces (Britt et al, ; Pajola et al, ; Steckloff et al, ; Steckloff & Samarasinha, ). OSIRIS observations show a direct evidence of the occurrence of a cometary landslide, with the resulting production of a newly formed boulder talus located at the base of the scarp (see the Aswan case; Pajola et al, ).…”
Section: Data Set: Identification Of Landslides On Comet 67pmentioning
confidence: 99%